Usia sebagai Faktor Risiko dari Tumor Ganas Osteosarkoma - Friska Desi Sabita; Yuni Prastyo Kurniati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Osteosarcoma is an invasive bone tumor malignancy, grows aggressively and has a high mortality rate. One of the risk factors for this cancer is age. On the other hand, industrial areas increase the risk of this disease. The purpose of this study was to analyze age and proximity to industrial areas as risk factors for osteosarcoma. This study used a case-control design. Osteosarcoma was the case group and Giant Cell Tumor of Bone was the control group. A total of 142 samples were taken from medical records of bone tumor histopathology preparations at the Pathology Anatomy Laboratory, Faculty of Medicine, UMS using the purposive sampling method. The age variable was divided into groups of 0-18 years and >18 years. The cut-off point for the distance to the industrial area was 2.5 km. The measurement data of the variables were analyzed using the Chi-square test. The results of the study showed an effect of age on the incidence of osteosarcoma (p value = 0.01); but there was no effect of distance to the industrial area on the incidence of osteosarcoma (p value = 0.369). The conclusion of the study shows that age is a risk factor for osteosarcoma.Keywords: osteosarcoma; age; risk factors ABSTRAK Osteosarkoma adalah keganasan tumor tulang yang bersifat invasif, berkembang secara agresif serta memiliki tingkat mortalitas yang tinggi. Salah satu faktor risiko dari kanker ini adalah usia. Di sisi lain, kawasan industri meningkatkan risiko penyakit ini. Tujuan penelitian ini adalah menganalisis usia dan kedekatan kawasan industri sebagai faktor risko kejadian osteosarkoma. Penelitian ini menggunakan desain case-control. Osteosarkoma merupakan kelompok kasus dan Giant Cell Tumor of Bone merupakan kelompok kontrol. Sejumlah 142 sampel diambil dari rekam medis sediaan histopatologi tumor tulang di Laboratorium Patologi Anatomi FK UMS dengan metode purposive sampling. Variabel usia terbagi menjadi kelompok 0-18 tahun dan >18 tahun. Cut off poin jarak terhadap kawasan industri adalah 2,5 km. Data hasil pengukuran variabel dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukkan adanya pengaruh usia terhadap kejadian osteosarkoma (nilai p = 0,01); namun tidak ada pengaruh jarak dengan kawasan industri terhadap kejadian osteosarkoma (nilai p = 0,369). Kesimpulan penelitian menunjukkan bahwa usia merupakan faktor risiko osteosarkoma.Kata kunci: osteosarkoma; usia; faktor risiko